History of the Louisville & Nashville Railroad - Klein, Maury, 1939- (Railroads of America (Macmillan), 2003)
"" After the Civil War, the Louisville & Nashville Railroad took the lead among southern railroads in developing rail systems and organizing transcontinental travel. Through two world wars, federal government control, internal crises, external dissension, the Depression, and the great Ohio River flood of 1937, the L & N Railroad remained one of the country's most efficient lines. It is a southern institution and a railroad buff's dream. When eminent railroad historian Maury Klein's definitive History of the Louisville & Nashville Railroad was first published in 1972, it quickly became one of.